Harpers biochemistry - Murray, Robert K.; etc. ([S.l.] : Appleton and Lange, 1987)
This book offers concise, yet authoritative coverage of the principles and latest advances in biochemistry and molecular biology as they relate to medicine.
International Edition.
Keywords: biochemistry,chemistry